Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1055/a-1342-7872
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30b-5p Influences Chronic Exercise Arthritic Injury by Targeting Hoxa1

Abstract: We identified the role of miR-30b-5p in chronic exercise arthritic injury. Rats with chronic exercise arthritic injury received treatment with miR-30b-5p antagomiR. H&E and Safranin O-fast green staining were performed. The levels of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were detected. The binding relationship between homeobox A1 (Hoxa1) and miR-30b-5p was revealed. After manipulating the expressions of miR-30b-5p and/or Hoxa1 in chondrocytes, the viability, apoptosis and migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Second, miR-30a/b promoted the inflammatory response and ECM degradation by enhancing the expression of IL-1β during chondrogenic differentiation 41 , 26 . Other evidence showed that miR-30b-5p increased the protein levels of MMP-13, cleaved caspase-3 and TNF-α in chondrocytes 37 . All these factors could strongly promote ECM degradation.…”
Section: Mir-30 Family and Arthritismentioning
confidence: 94%
See 2 more Smart Citations
“…Second, miR-30a/b promoted the inflammatory response and ECM degradation by enhancing the expression of IL-1β during chondrogenic differentiation 41 , 26 . Other evidence showed that miR-30b-5p increased the protein levels of MMP-13, cleaved caspase-3 and TNF-α in chondrocytes 37 . All these factors could strongly promote ECM degradation.…”
Section: Mir-30 Family and Arthritismentioning
confidence: 94%
“…Recently, studies confirmed that miR-30a/b was upregulated in OA cartilage samples, which promoted OA progression by inhibiting chondrocyte proliferation and differentiation, and promoting inflammation and extracellular matrix (ECM) degradation. First, miR-30b could downregulate the mRNA expression of collagen alpha-1(II) chain and aggrecan, which are key factors for cartilage proliferation and differentiation 37 . This effect was accomplished by targeting SOX9 38 , 39 and ERG (ETS-related gene) mRNA 40 .…”
Section: Mir-30 Family and Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth mentioning that miR-148a-3p promotes thrombospondin-4 expression and enhances angiogenesis during tendinopathy; miR-124 suppresses collagen formation of the human tendon [ 155 ], and miRNA124-3p directly binds and suppresses the expression of early growth response-1 (EGR1) and suppresses the synthesis of collagen during tenogenic differentiation (the transcription factor EGR1 promotes tendon repair and regulates tendon differentiation) [ 149 ]. miR-30b-5p is involved in cartilage degradation in rats with chronic exercise arthritic injury and regulates chondrocyte apoptosis and migration by targeting Hoxa1 [ 156 ]. Age-related cellular dysfunctions have been hypothesised to result in musculoskeletal age-related diseases, such as osteoarthritis, osteoporosis, and tendinopathy.…”
Section: Injury To Tendonsmentioning
confidence: 99%
“…HOXA1(Homeobox A1) is a member of HOX genes, belongs to the transcription factor family [7,8], which are highly conserved in evolution and are the main control genes of cell proliferation and differentiation, and participate in the growth and development of multiple human systems [9]. Studies have shown that miRNA (mir-18a-3p, mir-30b-5p) could target HOXA1 to regulate chondrocyte apoptosis and migration [10][11][12]. HOXA1 was also known to function in neural crest cell migration, posterior brain pattern, heart and ear development in mice and humans [13].…”
Section: Introductionmentioning
confidence: 99%